Sagot :
√x+3=7
[tex] \sqrt{ x} = 7 - 3[/tex]
[tex] \sqrt{x} = 4[/tex]
[tex]( \sqrt{x} ) ^{2} = {4}^{2} [/tex]
x = 16
√x+10=2
[tex] \sqrt{x} = 2 - 10 \\ \sqrt{x} = - 8 \\ {( \sqrt{x}) }^{2} = { (- 8)}^{2} [/tex]
x= 64
9=√x+7
[tex]9 - 7 = \sqrt{x} \\ \sqrt{x} = 2 \\ {( \sqrt{x}) }^{2} = {2}^{2} [/tex]
x = 4
3√x+ x²= 15+x²
[tex]3 \sqrt{x} + {x}^{2} - {x}^{2} = 15 \\ 3 \sqrt{x} = 15 \\ \sqrt{x} = 5 \\ { (\sqrt{x}) }^{2} = {5}^{2} [/tex]
x = 25
√x+5+1=3
[tex] \sqrt{x} + 6 = 3 \\ \sqrt{x} = 3 - 6 \\ \sqrt{x} = - 3 \\ {( \sqrt{x}) }^{2} = {( -3 )}^{2} [/tex]